(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The objective of the research is to study the influence of sex on the pain intensity, the impact of pain on emotional state (anxiety, depression),and the quality of life (mode state, ability to walk, usual daily activities, relationships, sleep, the will to live) and the differences between the two sexes. We hypothesize that the patient’s sexual background influences the intensity of pain. The impact of pain on the emotional state and also on the quality of life changes according to sex background and showing the differences between patients in the impact of pain on the emotional state or on the quality of life according to the severity of pain. Defining the relationship between the emotional state and the quality of life in all aspects. ﴾EVA﴿ scale was used to measure pain intensity, and ﴾HADS﴿ scale was used for the emotional state (anxiety, depression) and (QCD) scale which studies the impact of pain on the quality of life. We reviewed (22) cases of female patients and (20) cases of male patients, aged between (40 and 65), suffering from blood cancer (lymphoma and leukemia). The results showed that the average of pain intensity of both sexes is moderate. A significant difference is found between both sexes (for females) in pain intensity and in the impact of pain on anxiety. There were no significant differences between both sexes in the impact of pain of depression and the quality of life except the will to survive. There were no significant difference in the impact of pain on the quality of life according to the intensity of pain (weak, moderate, severe). A strong relationship is found between the emotional state (anxiety and depression) and the quality of life in all aspects.